Features of effective clustering in mining regions of Ukraine - Papizh, Yu. (Економічний вісник Донбасу, 2016)
Mining regions have specific features that should be fully integrated into the strategy ensuring their harmonious development. Methodological principles and concepts for the recovery and sustainable development of these regions should be elaborated by means of tools for clustering. The analysis of the cluster concept and patterns allowed identification of the reasons for not employing cluster models existing in various regions for mining areas in Ukraine. The article stresses the necessity of creating specific clusters for mining regions that will have new design given the factors of the spatial allocation of productive forces, organizational culture and dynamic changes in the integration processes undertaken by economic agents. Гірничодобувні регіони мають певні особливості, які повною мірою трансформуються в основу розробки стратегії забезпечення їх гармонійного розвитку. Формування методологічних засад концепції відновлення та забезпечення сталого розвитку цих регіонів має здійснюватися шляхом використання інструментарію кластеризації. На основі аналізу визначення сутності та моделей кластерів виявлено причини, за якими існуючі моделі кластерів не можуть бути використані для гірничодобувних регіонів України. Наголошено на необхідності створення для гірничодобувних регіонів кластерів нової форми із урахуванням факторів територіальної організації продуктивних сил, організаційної культури, динамічності змін та рівня інтеграції суб’єктів господарської діяльності. Горнодобывающие регионы имеют определенные особенности, которые в полной мере трансформируются в основу разработки стратегии обеспечения их гармоничного развития. Формирование методологических основ концепции восстановления и обеспечения устойчивого развития этих регионов должно осуществляться путем использования инструментария кластеризации. На основе анализа определения сущности и моделей кластеров выявлены причины, по которым существующие модели кластеров не могут быть использованы для горнодобывающих регионов Украины. Отмечена необходимость создания для горнодобывающих регионов кластеров новой формы с учетом факторов территориальной организации производительных сил, организационной культуры, динамичности изменений и уровня интеграции субъектов хозяйственной деятельности.